Physical Education as a Means of Social Inclusion for Students with Special Needs - Firayani, Firayani (Journal of Salutare, 2025)
Physical education has great potential as a means of social inclusion in the school environment, especially for students with special needs. This article aims to explore the role of physical education in building positive social interactions and strengthening a sense of togetherness among students with and without special needs. Using a qualitative approach, this study was conducted through in-depth interviews and participant observations in three inclusive schools in Indonesia. The results showed that physical education provides a participatory space that can reduce stigma, increase empathy, and facilitate collaboration between students. Physical activities that are designed in an inclusive manner encourage the active involvement of all students, which ultimately strengthens the social acceptance and self-confidence of students with special needs. This article emphasizes the importance of training physical education teachers on inclusive teaching strategies and providing facilities and infrastructure that are friendly to the disabled. Thus, physical education can be an effective medium in forming an inclusive school community that values diversity.